An insight into ion-conduction phenomenon of gold nanocluster ligand based metallo-supramolecular polymers. Issue 12 (7th March 2016) - Pandey, Rakesh K.; Chakraborty, Chanchal; Rana, Utpal; Moriyama, Satoshi; Higuchi, Masayoshi
Abstract : Gold nanocluster ligand and Fe(ii ) based metallo-supramolecular polymers (polyAuFe1 andpolyAuFe2 ) were synthesized. The polymers showed much higher conductance than the corresponding metallo-supramolecular polymer without gold nanoclusters. Abstract : A unique type of gold nanocluster ligand was prepared for metallo-supramolecular polymer synthesis. The nanocluster was capped with mercapto-phenyl-terpyridine and supramolecular polymers were prepared by complexation with Fe(ii ) salt. The obtained polymers exhibited a porous structure with high ionic conductivity. The ionic conductivity was found to be more than an order of magnitude higher than the polymer without gold nanoclusters.